Strategi Pemasaran Berbasis Kepuasan Pelanggan : Memahami Peran Kualitas Layanan dan Harga - Widiastuti, Tantri; Numberi, Agustinus (Jurnal Ilmiah Aset, 2024)
This study aimed to find out and describe the influence of service quality and price on customer satisfaction. Furthermore, in this study, customer satisfaction research focused only on the Salon “X”. The method of analysis in this study was regression test conducted by testing the effects of independent variables to the dependent variable. Analysis used in the study was quantitative analysis. Based on the testing and the discussion that has been done it can be concluded that testing the assumptions of classical test, which consisted of the test multikoliniarity, heteroscedasity test, and normality test didn’t show any indicators and disorders in the classical assumption test. While the results of multiple linear regression test that consisted of quality of service and price were independent variables simultaneously or F test had positive and significant impact on customer satisfaction. And partial or t test showed that the quality of service and price had a positive and significant impact on customer satisfaction at Salon “X”.